Engineering trustworthy software systems : second International School, SETSS 2016, Chongqing, China, March 28-April 2, 2016, Tutorial lectures /: second International School, SETSS 2016, Chongqing, China, March 28-April 2, 2016, Tutorial lectures. (2017) - Unknown
No abstract available